Determination of astragaloside III in rat plasma by liquid chromatography–tandem mass spectrometry and its application to a rat pharmacokinetic study. (1st July 2015) - Zhai, Yongsong; Li, Pengyue; Wang, Manyuan; Gong, Muxin; Qiu, Feng
Abstract: Astragaloside III (AST III), a naturally occurring saponin compound isolated from Radix Astragali, has been demonstrated to have anti‐gastric ulcer, immunomodulatory and antitumor effects. To evaluate its pharmacokinetics in rats, a rapid, sensitive and specific high‐performance liquid chromatography–tandem mass spectrometric (HPLC‐MS/MS) method has been developed and validated for the quantification of astragaloside III in rat plasma. Samples were pretreated using a simple protein precipitation with methanol–acetonitrile (50:50, v/v) and the chromatographic separation was performed on a C18 column by a gradient elution using a mobile phase consisting of water containing 0.1% formic acid and acetonitrile containing 0.1% formic acid. Astragaloside III and the internal standard (buspirone) were detected using a tandem mass spectrometer in positive multiple reaction monitoring mode. Method validation revealed excellent linearity over the range of 5.00–5000 ng/mL together with satisfactory intra‐ and inter‐day precision, accuracy and recovery. Stability testing showed that astragaloside III spiked into rat plasma was stable for 24 h at 20°C temperature, for up to 30 days at −80°C, and during three freeze–thaw cycles. The method was successfully used to investigate the pharmacokinetic profile of AST III after oral (10 mg/kg) and intravenous (1.0 mg/kg) administration in rats. The oral absolute bioavailability of AST III was calculated to be 4.15 ± 0.67% with an elimination half‐life value of 2.13 ± 0.11 h, suggesting its poor absorption and/or strong metabolism in vivo . Copyright © 2015 John Wiley & Sons, Ltd.